Apical Localisation of Crumbs in the Boundary Cells of the Drosophila Hindgut Is Independent of Its Canonical Interaction Partner Stardust - Kumichel, Alexandra (Public Library of Science, 2014)
The transmembrane protein Crumbs/Crb is a key regulator of apico-basal epithelial cell polarity, both in Drosophila and in vertebrates. In most cases studied so far, the apical localisation of Drosophila Crumbs depends on the interaction of its C-terminal amino acids with the scaffolding protein Stardust. Consequently, embryos lacking either Crumbs or Stardust develop a very similar phenotype, characterised by the loss of epithelial tissue integrity and cell polarity in many epithelia. An exception is the hindgut, which is not affected by the loss of either gene. The hindgut is a single layered epithelial tube composed of two cell populations, the boundary cells and the principal cells. Here we show that Crumbs localisation in the principal cells depends on Stardust, similarly to other embryonic epithelia. In contrast, localisation of Crumbs in the boundary cells does not require Stardust and is independent of its PDZ domain- and FERM-domain binding motifs. In line with this, the considerable upregulation of Crumbs in boundary cells is not followed by a corresponding upregulation of its canonical binding partners. Our data are the first to suggest a mechanism controlling apical Crumbs localisation, which is independent of its conserved FERM- and PDZ-domain binding motifs.